2017
DOI: 10.3389/fpls.2017.00839
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Genetic Diversity, Population Differentiation and Population Dynamics of Cycas segmentifida (Cycadaceae) Endemic to Southwest China by Multiple Molecular Markers

Abstract: Climate change, species dispersal ability and habitat fragmentation are major factors influencing species distribution and genetic diversity, especially for the range-restricted and threatened taxa. Here, using four sequences of chloroplast DNAs (cpDNAs), three nuclear genes (nDNAs) and 12 nuclear microsatellites (SSRs), we investigated the genetic diversity, genetic structure, divergence time and population dynamics of Cycas segmentifida D. Y. Wang and C. Y. Deng, a threatened cycad species endemic to Southwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 80 publications
2
21
0
Order By: Relevance
“…The Cycas species, with similar life history and reproductive characteristics, are thought to have a high level of genetic variation within populations and significant genetic differentiation among populations (Liu et al, 2015). The significant genetic differentiation and clear genetic structure observed in the C. taiwaniana complex may be explained by limited gene flow (Feng et al, 2014;James et al, 2018), which had also been reported for other Cycas species (Zhao and Gong, 2015;Feng et al, 2017). The effective propagation distance of Cycas species is 2-7 km (Yang and Meerow, 1996).…”
Section: Phylogeographical Patternmentioning
confidence: 86%
See 2 more Smart Citations
“…The Cycas species, with similar life history and reproductive characteristics, are thought to have a high level of genetic variation within populations and significant genetic differentiation among populations (Liu et al, 2015). The significant genetic differentiation and clear genetic structure observed in the C. taiwaniana complex may be explained by limited gene flow (Feng et al, 2014;James et al, 2018), which had also been reported for other Cycas species (Zhao and Gong, 2015;Feng et al, 2017). The effective propagation distance of Cycas species is 2-7 km (Yang and Meerow, 1996).…”
Section: Phylogeographical Patternmentioning
confidence: 86%
“…We selected the F81 model with a relaxed uncorrelated molecular clock for combined cpDNAs and an HKY+I model with a strict molecular clock for joint nDNAs. Because an accurate evolutionary rate for Cycas was unavailable, we applied the evolutionary rates for seed plants of 1.01 × 10 −9 substitutions per site per year for synonymous sites for cpDNA and 6.1 × 10 −9 (5.1-7.1 × 10 −9 ) substitutions per site per year for synonymous sites for SCNGs (Graur and Li, 2000;Feng et al, 2017). The MCMC analyses were run for 10 8 generations and was sampled every 10,000 steps.…”
Section: Phylogenetic and Molecular Dating Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimates of genetic diversity based on cpDNA sequences can be used to provide inferences on the evolutionary history of plant species, including possible recolonization routes, diversification events, and gene flow [18][19][20]. This approach has been used not only to analyze ecologically important species, such as those with a high degree of endemism [21], but also medicinal plants [22], and those with commercial potential [23].…”
Section: Introductionmentioning
confidence: 99%
“…A modified CTAB method was used to extract genomic DNA from silica‐gel dried leaf tissue (Doyle, 1991). Four cpDNA intergenic spacers, atpB‐rbcL (Sang & al., 1997), psbA‐trnH (Chiang & Peng, 1998), psbM‐trnD (Shaw & al., 2005), and trnS‐trnG (Shaw & al., 2005) and four nuclear genes, AC5 (actin 5 gene), PHYP (phytochrome P gene) (Feng & al., 2016a), PPRC (pentatricopeptide repeat‐containing protein gene) (Feng & al., 2017) and AAT (aspartate aminotransferase gene) were chosen for complete analysis. Primers are provided in Table 2.…”
Section: Methodsmentioning
confidence: 99%